Hubungan Dukungan Keluarga Dengan Tingkat Depresi Pada Narapidana Napza Dewasa Di Lembaga Permasyarakatan Narkotik Kelas II A - Asiah, Asiah; Rizkiyah, Laeli; Herlinawati (Jurnal Kesehatan Mahardika, 2024)
Background: Support from family is also one of the things that is needed to improve psychologically such as providing things that make you uplift or rise from the most difficult things that are being experienced. Depression is a sad mood disorder that lasts more than four weeks, which is accompanied by behaviors such as sleep changes, impaired concentration, irritability, very anxious, lack of enthusiasm, frequent crying, excessive alertness, pessimism, feeling worthless, and anticipating failure. Purpose: The aim is to determine the relationship between family support and adult drug prisoners in the Class II A Narcotics Correctional Institusion. Methods: This research design is a noncollerational experimental research design that uses a cross sectional approach. The population in this study was all drug inmates in the Class II A Narcotics Correctional Institusion according to adult criteria totaling 237 people with research samples that met the criteria in the study as many as 70 samples. The data collection method used a questionnaire with a random sampling sample using a questionnaire measuring instrument and the data was analyzed using the spearman rank test. Results: Family support for adult drug inmates in class II A Narcotics Correctional Institusion who received sufficient family support with 29 respondents (41.4%). While those who experienced mild depression with 25 respondents (35.7%). The results showed that a p value: 0.000 α: 0.05 meant that there was a relationship between family support and the level of depression in adult drug prisoners in class II A Narcotics Correctional Institusion. Conclusion: That there was a relationship between family support and the level of depression in adult drug prisoners in class II A Narcotics Correctional Institusion. The prison is expected to provide education or an agenda to gather families to discuss the condition or condition of prisoners and what actions must be taken by families to support and provide attention in order to reduce the fear experienced while undergoing the punishment process in prisons. Keywords: Drugs, Depression, Family Support, Narcotics Correctional Institusion